Patterns of Surveillance, Control, and Abuse Among a Diverse Sample of Intimate Partner Abuse Survivors. (December 2021) - Dardis, Christina M.; Ahrens, Courtney; Howard, Rebecca L.; Mechanic, Mindy B.
Using a mixed-methods design, the present study examined intimate partner surveillance among a diverse sample of intimate partner abuse (IPA) survivors ( n = 246), including women of Mexican ( n = 83), Korean ( n = 50), Vietnamese ( n = 49), and European descent ( n = 64). Most survivors (57%) described surveillance in either survey or interview; inductive thematic analysis revealed seven forms of surveillance. Finally, two-step cluster analysis identified two patterns of victimization most clearly differentiated by surveillance, but ethnic group differences in rates and patterns of abuse did not emerge. Implications for both clinicians and researchers are discussed.